The solution of the equation is x = 2
Step-by-step explanation:
The original equation is
![5x-10 = 0](https://tex.z-dn.net/?f=5x-10%20%3D%200)
We solve it using the following steps:
1) We apply the addition property of equality: by adding the same factor on both sides of the equation, the equation does not change.
In this case, we add +10 on both sides, and we get:
![5x-10+10=0+10\\5x=10](https://tex.z-dn.net/?f=5x-10%2B10%3D0%2B10%5C%5C5x%3D10)
2) We apply the division property of equality: by dividing both sides of the equation by the same number (different from zero), the equation does not change.
In this case, we divide both sides of the equation by 5, and we get:
![\frac{5x}{5}=\frac{10}{5}\\x=2](https://tex.z-dn.net/?f=%5Cfrac%7B5x%7D%7B5%7D%3D%5Cfrac%7B10%7D%7B5%7D%5C%5Cx%3D2)
Therefore, the solution of the equation is
.
Learn more about solving equations:
brainly.com/question/11306893
brainly.com/question/10387593
#LearnwithBrainly
Answer:
2
Step-by-step explanation:
The last number is 2
You calculate this by the only way the mean can be 4 is if the 3 numbers= up to 12. so 9 + 1=10 and if were looking for 12 we need 2 more so 2.
10 + 2=12
When dealing with mean you calculate the sum of all the number(check) then divided by the total of numbers so 3
12 divided by 3=4 and 4= your mean
Hope it helps have a great day:)
6×(1×5)=(6×1)×5
6×5=6×5
30=30
Always do the brackets first.
Follow BEDMAS
B = Brackets
E = Exponent
D = Division
M = multiplication
A = Addition
S = Substruction
Answer:
s(t) = 2t^2-3t
19 = 2t^2-3t
2t^2-3t-19=0
t = [3 +- sqrt(9-4*2*-19)]/4
t = [3 +- sqrt(161)]/4
t = [3 +- 12.6886]/4
Positive answer:
t = [3+12.6886]/4
t = 3.9221 seconds
Step-by-step explanation: